Optimizing Digital Public Services for Enhanced Citizen Satisfaction and Transparent Governance - Latip Latip; Dede Mirza; Novelma Lastri; Variza Aditiya (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Digital transformation has become a vital pillar in modernizing public service delivery worldwide, including in Indonesia. In the past five years, the government has increasingly adopted digital services to improve efficiency, reduce corruption, and foster participation. Yet, issues such as infrastructure gaps, digital illiteracy, and resistance to change hinder full optimization. This study aims to analyze strategies for strengthening digital public services to boost satisfaction while promoting transparent and accountable governance. A qualitative approach was employed using a structured literature review of ten scholarly articles published between 2017 and 2025. The literature was examined through content analysis, focusing on three themes: forms and structures of digital service implementation, impacts on citizen satisfaction, and contributions to governance quality. The findings indicate that successful digital transformation depends not only on infrastructure but also on institutional readiness, legal frameworks, citizen engagement, and inter-agency coordination. Digital services that emphasize accessibility, interactivity, and transparency foster trust and satisfaction. However, digital divides and unequal access remain significant obstacles. Ultimately, digitalization should align with principles of good governance to ensure inclusivity and strengthen relationships between citizens and the state while delivering meaningful improvements in service delivery and governance quality.